ANOMALI PRAKTIK SISTEM PEMERINTAHAN PRESIDENSIAL DAN MULTIPARTAI DI AWAL PEMERINTAHAN JOKOWI TAHUN 2014 - Yusuf Wibisono (Jurnal Ilmu dan Budaya, 2017)
This paper argues that although the presidential system of government in post-reform era has been refining the 1999 elections, but has not produced a stable and effective government. One of the main factors of effectiveness and stability of the government's problem is not caused by a combination of maximal system of government and the party system, the presidential and multiparty systems, not to support the creation of an effective and stable government. Nevertheless, we could not deny that the factors supporting fragile coalition government, the composition of the cabinet, the size structure of the coalition, the threat of impeachment, presidential prerogative is limited, political considerations, the dualism of loyalty, and the weak character of the national leadership also affects the effectiveness and stability of government. The thesis concludes that in order to create an effective and stable government in a presidential system of government with a mix of multi-party system, it would require a change in the political system in Indonesia. Presidential system of government can realize an effective and stable when combined with a simple party system, and supported by a solid coalition, and the application of the ideal presidential system of government and balanced.